Influence of kinesiophobia on activities of daily living of elder institutionalized persons with chronic pain - Milenković M.; Kocić M.; Balov B.; Stojanović Z.; Savić N.; Ivanović S. (Praxis Medica, 2015)
Aging of population leads to limitations in functional abilities and in activities of daily living (ADL) which are the essential elements of independent care of oneself. Limitations in performing these activities result in increasing need for assistance and institutionalizing of the elderly. The aim of this study was to investigate the influence of fear of movement, or kinesiophobia, on ADL in elder institutionalized people with chronic pain. The research included 60 individuals older than 65 suffering from chronic musculoskeletal pain, institutionalized in Gerontoloski Centar Nis. The participants' fear of movement was assesed by Tampa Scale of Kinesiophobia, performing ADL was assesed by Katz index and pain intensity was evaluated by Numerical Rating Scale. We found that a large number of participants had high degree of kinesiophobia (63%), as well as that there is statistically significant negative correlation between the values of Katz index and Tampa Scale (r=-0.583, p<0.01). There is no statistically significant negative correlation between the values of Numerical Rating Scale and Katz index (r=0.139, p<0.289). There is no statistically significant positive correlation between the values of Numerical Rating Scale and Tampa Scale (r=0.215, p=0.098). The research showed that kinesiophobia has influence on ADL in elder institutionalized people with chronic pain. Higher degree of fear of movement corresponds to greater dependence of the participants in performing ADL. Pain intensity influenced neither the fear of movement nor the dependence/independence in performing ADL.